KORELASI AKTIVITAS FISIK TERHADAP TINGKAT KECEMASAN PADA PENDERITA GANGGUAN KECEMASAN - Singkali, Dina Palayukan; Suwardiman, Suwardiman; Ramli, Kamrianti; Majiding, Chaidir Masyhuri (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Anxiety disorders are one of the most common forms of mental disorders found in society, and are not only experienced by adults, but also often occur in children and adolescents. The purpose of the study was to determine the correlation of physical activity with anxiety levels in patients with anxiety disorders. The research design used in this study was cross sectional. The research was conducted in 3 high schools in Tangerang City. The research was conducted in July 2024. The sample amounted to 101 students. The sampling technique used in this study was Simple Random Sampling. Data analysis was done univariate and bivariate. The results showed a relationship between physical activity (p value: 0.004) on the level of anxiety disorders in adolescents. It is recommended for adolescents to routinely do physical activity as an effort to maintain mental health.Keywords: Physical Activity, Anxiety, Adolescents.